Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.